Foreign Competition and Executive Compensation in the Manufacturing Industry: A Comparison between Germany and the U.S. - Katharina Dyballa; Kornelius Kraft (Institute of Labor Economics (IZA), 2018)
In this study we use import penetration as a proxy for foreign competition in order to empirically analyze (1) the impact of foreign competition on managerial compensation, (2) differences in the impact between Germany and the U.S and (3) whether the impact of import penetration is driven by implied efficiency effects. We use data from the manufacturing industry covering the period from 1984-2010 for Germany respectively 1992-2011 for the U.S and apply system GMM in order to solve potential endogeneity problems. It turns out that foreign competition leads to an increase of average per capita executive compensation in both countries. The impact of foreign competition on pay-performance sensitivity differs between the US and Germany. A differentiation between imported intermediates (efficient sourcing strategy) and final inputs (competition) reveals that the impact of import penetration is not biased by efficiency effects.
Keywords: F16; F14; G30; J33; 330; foreign competition; outsourcing; managerial incentives; international comparison; System GMM